Fast LC–MS/MS screening method for the evaluation of drugs, illicit drugs, and other compounds in biological matrices - Merone, G.M.; Tartaglia, A.; Rossi, S.; Santavenere, F.; Bassotti, E.; D'Ovidio, C.; Rosato, E.; de Grazia, U.; Locatelli, M.; Boccio, P. Del; Savini, F. (Talanta open, 2022)
•Fast LC–MS/MS screening method for compounds in biological matrices.•Blood, urine, and post mortem blood analyses.•Bioactive compounds, drugs and illicit drugs fast screening analyses.•Innovative configurations to maximize the instrumental performances.•Green Analytical Procedure Index (GAPI) evaluation. Nowadays it is increasingly important from a pharmacological, toxicological, and clinical point of view to have rapid and reliable screening tests available for the analysis of numerous compounds in very short time. Often these procedures involve innovative and eco–friendly extraction and purification techniques, but it is necessary to apply preliminary steps such as the protein precipitation (plasma or whole blood) or enzymatic hydrolysis, to obtain a quantitative dosage also of the metabolites (urine). In this work a rapid screening procedure in liquid chromatography coupled with tandem mass spectrometry (LC–MS/MS) for the qualitative evaluation of 739 compounds in biological samples (blood, post–mortem blood, and urine) has been reported. The method also considers the deuterated internal standards (d9–methadone and d3–monohydroxycarbazepine) to monitor the performances of the screening (check of the fragmentation process and retention times). The procedure involves two separate analyses in positive and negative ionization and a chromatographic run of 18 min, without modifying the instrumental parameters (except the ionization polarity of the turbospray source). The chromatographic separation was carried out using a Restek Allure PFP Propyl (5 µm, 60Å, 50 × 2.1 mm) column in gradient elution mode. The instrument works in Multiple Reaction Monitoring (MRM) mode on 697 specific transitions for the compounds subject to screening. Furthermore, real samples (human blood and urine) were analyzed to confirm the correct performance of the screening. [Display omitted]